Effect of maturity status on force-velocity relationships in a ballistic lower limb test in high-level soccer players - Galantine, P.; Bertin, D.; Duché, P.; Hays, A. (Journal of Sports Sciences, 2024)
This study aimed to investigate the effect of maturity status on force-velocity relationships in a ballistic lower limb (BLL) test in high-level soccer adolescents and young adults. The population was 61 adolescents (13.0-17.9 years) and 23 young adults (18.0-26.2 years). Subjects completed the BLL test on a ballistic ergometer equipped with two force plates and a linear encoder. Following Samozino`s method, maximal power output (Pmax), force (F0) and velocity (v0) were determined. An allometric model was applied to Pmax and F0 with body mass (BM) and fat-free mass (FFM). Significant effects of maturity status were found for absolute Pmax, F0, relative Pmax to BM and FFM, relative F0 to FFM and F0 allometrically scaled to BM and FFM (p = 0.02 to p < 0.001; Eta = 0.10 to Eta = 0.49). There was no significant effect for Pmax allometrically scaled to BM and FFM, F0 relative to BM and v0. Body dimensions explain group differences in Pmax whereas for F0, qualitative factors explain the differences between the groups. As maturity status and body dimensions influence Pmax, these factors should be considered when assessing explosive short efforts. This could help to better identify potential athletic talent and adapt training content.